2018
DOI: 10.1016/j.bbalip.2018.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Oxygenation of polyunsaturated fatty acids and oxidative stress within blood platelets

Abstract: The oxygenation metabolism of arachidonic acid (ArA) has been early described in blood platelets, in particular with its conversion into the potent labile thromboxane A that induces platelet aggregation and vascular smooth muscle cells contraction. In addition, the primary prostaglandins D and E have been mainly reported as inhibitors of platelet function. The platelet 12-lipoxygenase (12-LOX) product, i.e. the hydroperoxide 12-HpETE, appears to stimulate platelet ArA metabolism at the level of its release fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 85 publications
1
23
0
Order By: Relevance
“…The pro-oxidative conditions observed in both forms of psoriasis should result in ROS reactions with nucleophilic compounds, including lipids and proteins, causing their oxidative modifications. Particularly susceptible to oxidative modifications are PUFAs, which occur either bound to phospholipids or as free molecules, in biomembranes and are metabolized in ROS-dependent and in enzymes-catalyzing reactions [4]. The results obtained in our study have shown that levels of PUFAs decrease in both forms of psoriasis, but more in the case of PsA, which had more pronounced onset of oxidative stress, as discussed already.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The pro-oxidative conditions observed in both forms of psoriasis should result in ROS reactions with nucleophilic compounds, including lipids and proteins, causing their oxidative modifications. Particularly susceptible to oxidative modifications are PUFAs, which occur either bound to phospholipids or as free molecules, in biomembranes and are metabolized in ROS-dependent and in enzymes-catalyzing reactions [4]. The results obtained in our study have shown that levels of PUFAs decrease in both forms of psoriasis, but more in the case of PsA, which had more pronounced onset of oxidative stress, as discussed already.…”
Section: Discussionsupporting
confidence: 78%
“…Therefore, cellular redox homeostasis plays a key role in physiology of the cells as well as in numerous pathophysiological processes. Elevated ROS levels that cannot be counteracted by the cellular antioxidant abilities induce redox imbalance leading to oxidative stress [1,3], further causing oxidative modifications in the structure and function of cellular components, in particular of the unsaturated biomembrane lipids [4]. The consequence is an increase of the products of ROS-dependent oxidative fragmentation as well as cyclisation of fatty acids [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The pro-oxidative conditions observed in both forms of psoriasis should result in ROS reactions with nucleophilic compounds including lipids and proteins, which causes their oxidative modifications. Particularly susceptible to oxidative modifications are PUFAs, which are either bound to phospholipids or as free molecules, in bio-membranes and are metabolized in ROS-dependent and in enzyme-catalyzing reactions [ 4 ]. The results obtained in our study have shown that levels of PUFAs decrease in both forms of psoriasis but more in the case of PsA, which had more pronounced onset of oxidative stress, as discussed earlier.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, cellular redox homeostasis plays a key role in physiology of the cell as well as in numerous pathophysiological processes. Elevated ROS levels that cannot be counteracted by the cellular antioxidant abilities induce a redox imbalance that leads to oxidative stress [ 1 , 3 ], which further causes oxidative modifications in the structure and function of cellular components especially of the unsaturated bio-membrane lipids [ 4 ]. The consequence is an increase of the products of ROS-dependent oxidative fragmentation as well as cyclization of fatty acids [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…When the level of ROS exceeds the antioxidant capacity of cells, lipids can react with ROS to reinstate the cellular redox homeostasis as well. Under oxidative stress, oxidants attack lipids containing C-C bond(s), particularly polyunsaturated fatty acids [19,20]. Since yeast does not contain polyunsaturated fatty acids, there is no lipid peroxidation process in its cells.…”
Section: Introductionmentioning
confidence: 99%